2006
DOI: 10.1177/0145445503259390
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Strategies for Constructing Nonviolent Cultures With Youth

Abstract: Youth violence is widely recognized as a critical social issue in the United States, and many approaches to prevention have been developed in recent years. Emerging research suggests that only approaches that are deeply embedded in cultural, community, and organizational contexts are likely to be powerful enough to have a meaningful collective impact. No programs of this kind that are also truly practical and socially valid have yet reached a level where they can be regarded as well established, but data are b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 66 publications
(77 reference statements)
0
12
0
Order By: Relevance
“…While many schools focus on security utilizing surveillance, metal detectors, and increased police presence, others have suggested that schools should focus on the impact of school culture (Mattaini & McGuire, 2006;Heinen et al, 2007;Coyle, 2008;Bosworth & Judkins, 2014). Creating safe school environments using security techniques help students and faculty feel safe; however, these techniques do little to change the environment that cultivates violent behavior (May, 2014).…”
Section: Rationalmentioning
confidence: 99%
“…While many schools focus on security utilizing surveillance, metal detectors, and increased police presence, others have suggested that schools should focus on the impact of school culture (Mattaini & McGuire, 2006;Heinen et al, 2007;Coyle, 2008;Bosworth & Judkins, 2014). Creating safe school environments using security techniques help students and faculty feel safe; however, these techniques do little to change the environment that cultivates violent behavior (May, 2014).…”
Section: Rationalmentioning
confidence: 99%
“…Unfortunately social organizations seem to have ignored or to be unaware of the findings of behaviour analysts' which warn against social coercion and instead promote alternative ways of social control (Ballesteros de Valderrama 2000;Mattaini 2003Mattaini , 2006Mattaini and Addams 2001;Mattaini and McGuire 2006). In this respect, it is worth mentioning other theoretical perspectives that are compatible with this line of thinking: Arendt (1987), Freire (2004), ), Habermas (2003, Lederach (1998), andMartín-Baró (2003).…”
Section: An Issue Of Human Actionmentioning
confidence: 99%
“…Cultural practices (not individual persons) survive over time as a result of natural selection by differential consequences. Such practices involve interlinked contingencies of reinforcement in which the behavior and resultant products of each person function as environmental events that influence others (e.g., Biglan, 1995; Biglan, Flay, Embry, & Sander, 2012; Glenn, 1991; Mattaini & McGuire, 2006). For each cultural practice, we can ask: Who is involved?…”
Section: The Language and Conceptual Understanding Of Learningmentioning
confidence: 99%